PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT INDOKACA MITRA FORTUNA - Benny, Benny; Nora Pitri Nainggolan (LPPM Universitas Putera Batam, 2022)
The purpose of this research is find out how the influence of brand image and servicequality on customer satisfaction at PT Indokaca Mitra Fortuna with saturated samplingtehcniques that are all existing customers so as to get a sample number of 104 respondens.The method of collecting data is by a questionaire that is distributed directly. Data qualitytest in this study using validity test and reliabilty test, classic assumption test and influencetest in this study using coefficient of determination analysis and multiple linear regressionanalysis, while hypothesis test in this study using (t test) and (F test) using SPSS softwareprogram version 26. The result of coeffiicient of determination (R2) obtained is the variablebrand image and service quality affects 78.6% of customer satisfaction. from the results oft and f tests, it could be concluded that partially the brand image and service quality has asignifiicant effect on customer satisfaction, as well as simultaneously the brand image andservice quality have a significant effect on customer satisfaction.